Tuesday

July 22, 2014

July 22, 2014

Posted by **jacob** on Wednesday, September 25, 2013 at 11:14am.

Original Equation: 2 + 3y = 5(y - 2)

Step One: 2 + 3y = 5y - 10

Step Two: 2 = 2y - 10

Step Three: -8 = 2y

Step Four: -4 = y y = -4

1

2

3

4

- Algebra -
**Mary**, Wednesday, September 25, 2013 at 11:31amStep 2: because instead of adding the like terms he subtracted them

- Algebra -
**Jai**, Wednesday, September 25, 2013 at 11:31amStep 1 & 2 are right. She made the first mistake in Step 3, it should be

2 + 10 = 2y

12 = 2y

And so the succeeding steps are wrong too. But the earliest was in step 3.

hope this helps :3

**Related Questions**

math - ..... Amy finished 6/12 of the problems on her timed test. Jackson ...

Quick math question - Can anyone give me a link to a free online algebra test ...

Math - Amy finished 6/12 of the problems on her timed test. Jackson finished 4/6...

Stats - On her first test in algebra, Mary earned a score of 75, and she made an...

Algebra 1 - 4. Two consultants were hired by a company. The total consultant ...

Algebra - I am going to take an Accuplacer math placement test later this week. ...

Geometry Part 2 - At a track meet,50 people ran the 100- meter dash.2 people ...

Algebra - how do I solve this M/6 - 7 = 2/3

algebra - f(t)=sqrtt^2+1 f(-9)=sqrt-0^2+1

algebra - Solve x+3y=12